The Influence of Event Organizer Service Performance in Achieving Customer Satisfaction Through Professionalism and Emotional Intelligence as Intervenings in the Event Organizer Service Industry - M. Dzikri Abdul Rohman; Zahera Mega Utama; Jubery Marwan (PT. Mega Mas Abadi Konsultan, 2025)
This study aims to examine and analyse the impact of event organiser service performance on customer satisfaction, with professionalism and emotional intelligence serving as intervening variables. The research was conducted among event organiser service firms in South Tangerang City and classified as explanatory research employing a quantitative approach. Primary data were collected through questionnaires and subsequently tested for validity, reliability, and normality to ensure data accuracy and consistency. The sampling technique applied was saturated sampling, involving all members of the population, and the analytical method used was path analysis to determine both direct and indirect effects between variables. The findings indicate that event organiser service performance, professionalism, and emotional intelligence have a significant influence on customer satisfaction. Furthermore, service performance indirectly affects customer satisfaction through the mediating roles of professionalism and emotional intelligence. The results highlight that professionally competent employees who possess strong emotional intelligence are more capable of managing their emotions, maintaining composure in challenging situations, and fostering effective communication and collaboration within teams. These qualities contribute to creating a positive work atmosphere that enhances service quality. Consequently, customers experience higher satisfaction when they are served sincerely, empathetically, and with a deep understanding of their needs, thereby strengthening the overall service performance of event organiser firms.